2023
DOI: 10.3390/antiox12081558
|View full text |Cite
|
Sign up to set email alerts
|

Partial Purification and Biochemical Evaluation of Protease Fraction (MA-1) from Mycoleptodonoides aitchisonii and Its Fibrinolytic Effect

Abstract: The antioxidative proteolytic fraction, MA-1, was partially purified from Mycoleptodonoides aitchisonii. MA-1 was purified to homogeneity using a two-step procedure, which resulted in an 89-fold increase in specific activity and 42.5% recovery. SDS-PAGE revealed two proteins with a molecular weight of 48 kDa. The zymography results revealed proteolytic activity based on the MA-1 band. MA-1 was found to be stable in the presence of Na+, Ca2+, Fe3+, K+, and Mg2+. MA-1 was also stable in methanol, ethanol, and ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
(58 reference statements)
0
1
0
Order By: Relevance
“…According to the study conducted by Kim et al [43], it was observed that the fibrinolytic enzyme derived from Cordyceps militaris initially targeted the Aα chains of fibrinogen for hydrolysis, followed by subsequent hydrolysis of the γ and Bβ chains. A fibrinolytic enzyme, MA-1, purified from Mycoleptodonoides aitchisonii [44] first hydrolyzed the Aα chain of fibrinogen, then the γ and Bβ chains.…”
Section: Fibrin(ogen)olytic Activity Of Cfementioning
confidence: 99%
“…According to the study conducted by Kim et al [43], it was observed that the fibrinolytic enzyme derived from Cordyceps militaris initially targeted the Aα chains of fibrinogen for hydrolysis, followed by subsequent hydrolysis of the γ and Bβ chains. A fibrinolytic enzyme, MA-1, purified from Mycoleptodonoides aitchisonii [44] first hydrolyzed the Aα chain of fibrinogen, then the γ and Bβ chains.…”
Section: Fibrin(ogen)olytic Activity Of Cfementioning
confidence: 99%